2022
DOI: 10.3390/molecules27196679
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Synthesis of an Oxovanadium(IV)-bis(abietate) Complex with Antimicrobial Action

Abstract: The search for less expensive and viable products is always one of the challenges for research development. Commonly, the synthesis of coordination compounds involves expensive ligands, through expensive and low-yield routes, in addition to generating toxic and unusable residues. In this work, the organic ligand used is derived from the resin of a reforestation tree, Pinus elliottii var. elliottii. The synthesis method used Pinus resin and an aqueous solution of vanadium(III) chloride at a temperature of 80 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The recrystallized salt was characterized and applied as an antimicrobial agent against fungi and bacteria. The salt has been used as a precursor ligand in the preparation of coordination compounds with transition metals [ 9 , 10 ]. The resulting compounds have different colors depending on the metal used, as well as antimicrobial properties when used as pigments in commercial white paint.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The recrystallized salt was characterized and applied as an antimicrobial agent against fungi and bacteria. The salt has been used as a precursor ligand in the preparation of coordination compounds with transition metals [ 9 , 10 ]. The resulting compounds have different colors depending on the metal used, as well as antimicrobial properties when used as pigments in commercial white paint.…”
Section: Resultsmentioning
confidence: 99%
“…No matching files were found in the Inorganic Crystal Structure Database (ICSD), International Centre for Diffraction Data (ICDD), and Crystallography Open Database (COD). The initial analysis of the X-ray diffraction profile showed that Na abietate has a structure characteristic of a non-crystalline molecular substance [ 9 , 10 ], with broad diffraction peaks and low intensity. The degree of crystallinity was found to be around 52%, with a crystallite size of 21.9 Å.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations